2022
DOI: 10.3390/biomedicines10071687
|View full text |Cite
|
Sign up to set email alerts
|

Differential Neuropathology, Genetics, and Transcriptomics in Two Kindred Cases with Alzheimer’s Disease and Lewy Body Dementia

Abstract: Alzheimer’s disease (AD) and Lewy body dementia (LBD) are two different forms of dementia, but their pathology may involve the same cortical areas with overlapping cognitive manifestations. Nonetheless, the clinical phenotype is different due to the topography of the lesions driven by the different underlying molecular processes that arise apart from genetics, causing diverse neurodegeneration. Here, we define the commonalities and differences in the pathological processes of dementia in two kindred cases, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The expression of cholinergic receptors, CHRM1 and CHRM4, have also been shown to be upregulated in AD when compared to DLB [102]. Further research has demonstrated that the transcriptomic differences between AD and those with Lewy pathology is dependent on brain region [103]. Transcriptional dysregulation appears to correlate with neurodegeneration, and individuals with Lewy pathology are likely to experience dysregulation in the substantia nigra, whilst cases of AD are more likely to show dysregulation in the parietal lobe [103].…”
Section: Transcriptomic Comparison With Other Dementias and Synuclein...mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of cholinergic receptors, CHRM1 and CHRM4, have also been shown to be upregulated in AD when compared to DLB [102]. Further research has demonstrated that the transcriptomic differences between AD and those with Lewy pathology is dependent on brain region [103]. Transcriptional dysregulation appears to correlate with neurodegeneration, and individuals with Lewy pathology are likely to experience dysregulation in the substantia nigra, whilst cases of AD are more likely to show dysregulation in the parietal lobe [103].…”
Section: Transcriptomic Comparison With Other Dementias and Synuclein...mentioning
confidence: 99%
“…Further research has demonstrated that the transcriptomic differences between AD and those with Lewy pathology is dependent on brain region [103]. Transcriptional dysregulation appears to correlate with neurodegeneration, and individuals with Lewy pathology are likely to experience dysregulation in the substantia nigra, whilst cases of AD are more likely to show dysregulation in the parietal lobe [103]. Further research is warranted to determine how DLB differs from other dementias and synucleinopathies across the brain region to improve molecular understanding and facilitate accurate diagnosis.…”
Section: Transcriptomic Comparison With Other Dementias and Synuclein...mentioning
confidence: 99%
“…Alzheimer's disease, for example, is caused by a number of genetic mutations and epigenetic regulations. (PSEN1; PSEN2; APP; APOE ε4; TREM2; SORL1; ABCA7; CR1; DAPK1; CLU; PICALM; BIN1; MS4A6A; CD33; CD2AP; EPHA1; miR-124; miR-15 et miR-146a) [8] and Lewy body dementia (LBD) (GBA, SNCA, APOE, CNTN1, BCL7C/STX1B, T. M. Zohoncon SCARB2 [9], miR-24-3p, miR-25-3p, miR-3p, miR-361-5p, miR-425x5p, et miR-451a [10]. Whereas Huntington's disease is caused by an expansion of the polymorphic CAG trinucleotide by more than 35 repeats in exon 1 of the HTT gene [11].…”
Section: Introductionmentioning
confidence: 99%